On mortis causa transactions in Roman Law and Spanish Civil Law: proposals for a definition in each area and for the concept of terminus iuris - Satrústegui Caruncho, Rafael (Cuadernos de Historia del Derecho, 2025)
This paper presents an analysis of mortis causa legal transactions in Roman Law and Spanish Civil Law, from the perspective of the juridical dogmatism, aiming to provide a precise definition for each domain. The study begins by reviewing Jordano Barea’s critique of the predominant doctrinal conception of the will, examining the private nature of mortis causa institutions, assessing the legal effects they might produce immediately, and the role of a condicio iuris within them. Throughout the discussion, the implicit presence of the concept of terminus iuris in both legal systems becomes apparent. Finally, the paper culminates in proposed definitions.